Emission analysis of CuO2 nanoparticle addition with blend of Botryococcus braunii algae biodiesel on CI engine. (2020) - Dharmaprabhakaran, T.; Karthikeyan, S.; Periyasamy, M.; Mahendran, G.
Abstract: The energy crisis is due to two reasons: one is the rapid growth of the global human population, and the other is the transformation of the residing human style. Traditional fuel is also a major component of adding pollutants to the environment. Changes in fuel consumption play a major role in increasing engine efficiency and reducing emissions. In the current research, fuel changes in the diesel engine were developed. The single-cylinder diesel engine was initially equipped with Botryococcus braunii algae oil methyl ester and its diesel blends with CuO2 nano additives B20, B20 + 25 ppm, B20 + 50 ppm, B20 + 75 ppm, B20 + 100 ppm at different loads at steady engine speed. From the experimental analysis, it has been shown that B20 is the more efficient fuel ratio than other blends. The results showed a significant reduction in CO, HC and smoke emissions. The current analysis shows that BBAME's biodiesel with CuO2 nano additives is best suited as an alternative diesel engine fuel.